Schwannoma of the penis, presenting as a scrotal mass, rare entity with an uncommon presentation - Ujwal Kumar; Nawal Kishore Jha (Urology Annals, 2017)
Schwannomas are benign nerve sheath tumors that are seen either sporadically or in patients of neurofibromatosis. This tumor is common in head, neck, and extremities. Penis is a rare site for this tumor. To the very best of our knowledge, <34 cases of penile schwannoma have been reported in literature till now, but none had presented as scrotal mass. Here, we report a case of penile schwannoma in a 16-year-old male boy who presented in our outpatient department with a slowly growing scrotal mass. Our patient did not have any other feature of neurofibromatosis. The patient after investigation underwent surgical excision and had no recurrence on follow-up of 5 years.